The Survivance in the Literature of the First Nations in Canada - Christophe Premat (Baltic Journal of English Language, Literature and Culture, 2019)
The article examines the way the writers of the First Nations in Canada deal with the issue of survivance which implies a collective resilience. It is based upon a comparison between the first novel of Naomi Fontaine, Kuessipan (2011) and the poetry of Rita Mestokosho collected in How I see Life, Grandmother, Eshi Uapataman Nukum, Comment je percois la vie, grand-mere (2011). Both writers belong to a tradition of litterature autochtone in Quebec that has become more and more visible since the 1980s. If both writers share the paradigm of decoloniality, their aesthetics remains classical with the use of a minimalist style to express the beauty of the Innu way of life.